Primary source of income is associated with differences in HIV risk behaviors in street-recruited samples - Fernández-Esquer Maria E; Meshack Angela F; Williams Mark L; Ross Michael W; Essien E James; Peters Ronald J; Ogungbade GO (BMC, 2004)
Abstract Background The relationship between primary source of income and HIV risk behaviors and the racial/ethnic differences in risk behavior profiles among disadvantaged populations have not been fully explored. This is unusual given that the phenomenon of higher risk in more disadvantaged populations is well-known but the mechanisms remain unclear. We examined the relationship between primary source of income and differences in HIV risk behaviors among four racial/ethnic groups in the southern United States. Methods Self-reported data on primary source of income and HIV risk behaviors were collected from 1494 African American, Hispanic, Asian, and White men and women in places of public congregation in Houston, Texas. Data were analyzed using calculation of percentages and by chi-square tests with Yates correction for discontinuity where appropriate. Results Data revealed that a higher proportion of whites were involved in sex for money exchanges compared to the other racial groups in this sample. The data suggest that similar street sampling approaches are likely to recruit different proportions of people by primary income source and by ethnicity. It may be that the study locations sampled are likely to preferentially attract those involved in illegal activities, specifically the white population involved in sex for drug or money exchanges. Research evidence has shown that people construct highly evolved sexual marketplaces that are localized and most unlikely to cross racial, ethnic, and socioeconomic or geographical boundaries. Thus, the areas that we sampled may have straddled a white sexual marketplace more than that of the other groups, leading to an over-representation of sex exchange in this group. Drug use was highest among those with illegal primary sources of income (sex exchange and drug dealing and theft), and they were also those most likely to have injected drugs rather than administered them by any other route (p < 0.001). In addition, bisexual or homosexual identification was reported by more respondents in the sex exchange as primary source of income category. The number of sexual partners in the last three months followed a similar pattern, with those whose primary source of income was drug dealing or theft reporting relatively high partner numbers. Conclusions These data suggest that social disadvantage is associated with HIV risk in part by its association with drug and sex work for survival, and offers one variable that may be associated with the concentration of disease among those at greatest disadvantage by having an illegal and unstable primary income source.